The Investigation of the Relationship between Financial Leverage and Return on Supply Chain Management - Mohammadzadeh Moghadam, Hassan; Faghani, Mehdi; Heydari, Mostafa (ExcelingTech, 2019)
Abstract—The objective of the present study was to investigate the relationship between financial leverage and return on supply chain management and assest of the rural cooperatives. In this study, five ratios have been selected as financial leverage including total debt to total assets, total debt to total shareholders' equity, total long-term debt to total assets, total short-term debt to total assets and total debt to total capital. The return on asset is also calculated from the total debt to annual profit ratio. According to the objective of the research, this work is an applied research and according to the data collection method, it is a descriptive correlational study. The population included all rural cooperatives in the eastern part of the country in which 153 cooperatives were selected using the elimination method. Data analysis and the hypothesis testing were performed by simple linear regression test and using SPSS software. The results showed that three financial leverages have significantly affected the return on assets of the cooperatives which are the total debt to total assets, total long-term debt to total assets, and total short-term debt to total assets ratios. Of these three ratios, the total debt to total assets (-0.304) has the greatest effect on the return in assets of the cooperatives. The two other financial leverage ratios, i.e., the total debt to total shareholders' equity and the total debt to total capital did not have a significant effect on the return on assets of the rural cooperatives in the eastern part of the country. Thus, it is recommended to the cooperatives' Chief Executive Officer to focus more on three ratios of total debt to assets, total long-term debt to total assets, and total short-term debt to total assets in order to increase the return on equity of the cooperative and plan on the financial focus of the cooperative to reduce these ratios based on the efficient supply chain system.